2021
DOI: 10.3390/ijms22041512
|View full text |Cite
|
Sign up to set email alerts
|

Additive Behavioral Improvement after Combined Cell Therapy and Rehabilitation Despite Long-Term Microglia Presence in Stroke Rats

Abstract: Microglia are involved in the post-stroke immunomodulation of brain plasticity, repair, and reorganization. Here, we evaluated whether adipose-tissue-derived mesenchymal stem cells (ADMSCs) and/or rehabilitation improve behavioral recovery by modulating long-term perilesional inflammation and creating a recovery-permissive environment in a rat model of ischemic stroke. Methods: A two-way mixed lymphocyte reaction was used to assess the immunomodulatory capacity of ADMSCs in vitro. Two or 7 days after permanent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…Improvement of the health condition of experimental animals after ischemic or inflammatory damage of the CNS has been reported with many types of cells and is not limited to human neural stem cells (Mine et al 2013), rat neural stem cells (Mitrečić et al 2010) and adipose tissue mesenchymal cells (Bakreen et al 2021). To test if accelerated and/or improved recovery can be induced by hOSMCs, we transplanted 1 million of hOMSCs to animals in which stroke was induced by MCAO.…”
Section: Discussionmentioning
confidence: 99%
“…Improvement of the health condition of experimental animals after ischemic or inflammatory damage of the CNS has been reported with many types of cells and is not limited to human neural stem cells (Mine et al 2013), rat neural stem cells (Mitrečić et al 2010) and adipose tissue mesenchymal cells (Bakreen et al 2021). To test if accelerated and/or improved recovery can be induced by hOSMCs, we transplanted 1 million of hOMSCs to animals in which stroke was induced by MCAO.…”
Section: Discussionmentioning
confidence: 99%
“…The adult mammalian brain is more plastic following injury, indicating a window of opportunity to intervene with therapeutics [ 261 ]. This combination therapy is relatively unexplored; however, animal studies show promise [ 70 ].…”
Section: Remodeling Of Stroke Tissue Microenvironment Outside the Brainmentioning
confidence: 99%
“…In a follow-up preclinical study, MSCs were again evaluated with EE after MCAO and confirmed the significantly improved behavioral outcome seen with combination therapy. The rats were given MSCs two and seven days after stroke with continuous EE and evaluated on day 46 with substantial functional recovery and the presence of long-term microglia in the penumbra [ 70 ]. Replacement of lost neurons will not be enough to aid in functional recovery.…”
Section: Remodeling Of Stroke Tissue Microenvironment Outside the Brainmentioning
confidence: 99%
See 2 more Smart Citations